2022
DOI: 10.1001/jamanetworkopen.2021.41927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncologic Outcomes and Treatment-Related Toxicity of Carbon Ion Radiotherapy and En Bloc Resection for Sacral Chordoma

Abstract: IMPORTANCE Maximal resection is the preferred management for sacral chordomas but can be associated with unacceptable morbidity. Outcomes with radiotherapy are poor. Carbon ion radiotherapy (CIRT) is being explored as an alternative when surgery is not preferred. OBJECTIVE To compare oncologic outcomes and treatment-related toxicity of CIRT and en bloc resection for sacral chordoma. DESIGN, SETTING, AND PARTICIPANTSUnivariable logistic regression was performed to evaluate the association between treatment type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Yolcu et al compared the oncologic outcomes and treatment-related toxicity of CIRT with those of patients undergoing en bloc resection. They found that CIRT can be applied to patients without surgery or older patients with high-performance status and may also provide benefits for patients with margin-positive resection[36]. These studies shed light on the potential benefits of adjuvant radiotherapy for chordoma patients and emphasize the need for further exploration. Fundamental and Clinical Trial Investigation: A primary focus of fundamental research involves exploring the in vitro gene expression of chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…Yolcu et al compared the oncologic outcomes and treatment-related toxicity of CIRT with those of patients undergoing en bloc resection. They found that CIRT can be applied to patients without surgery or older patients with high-performance status and may also provide benefits for patients with margin-positive resection[36]. These studies shed light on the potential benefits of adjuvant radiotherapy for chordoma patients and emphasize the need for further exploration. Fundamental and Clinical Trial Investigation: A primary focus of fundamental research involves exploring the in vitro gene expression of chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since April 2016, carbon ion radiotherapy has been available for unresectable/inoperable BSTS in Japan. Following that, proton beam therapy has also been available since April 2018, and in recent years, clinically favorable results for particle beam therapy (carbon ion and proton beam) with regard to unresectable/inoperable BSTSs have been reported [ 12 , 13 , 14 , 15 , 16 , 17 ], especially for chordomas [ 12 , 18 , 19 , 20 ]. However, the long-term outcome of particle beam therapy for BSTS is unclear; therefore, the standard treatment for BSTS, except for chordoma, is still surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…31 Carbon ion therapy, a powerful form of radiotherapy with limited worldwide availability, probably has benefit for marginpositive surgical cases or definitive treatment in older patients. 32 At present, there remains considerable variation between centres in how these tumours are approached with regard to the use of radiotherapy, the surgical approach, and planned surgical margin. 33 The above discussion applies to patients with a primary chordoma of the sacrum.…”
Section: Primary Sacral Tumoursmentioning
confidence: 99%